2010
DOI: 10.1021/ja100739h
|View full text |Cite
|
Sign up to set email alerts
|

Computational Explorations of Mechanisms and Ligand-Directed Selectivities of Copper-Catalyzed Ullmann-Type Reactions

Abstract: Computational investigations of ligand-directed selectivities in Ullmann-type coupling reactions of methanol and methylamine with iodobenzene by β-diketone-and 1,10-phenanthroline-ligated Cu(I) complexes are reported. Density functional theory (DFT) calculations with several functionals were performed on both the nucleophile formation and aryl halide activation steps of these reactions. The origin of ligand-directed selectivities in N-vs. O-arylation reactions as described in a previous publication (J. Am. Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
234
2
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(257 citation statements)
references
References 82 publications
10
234
2
11
Order By: Relevance
“…The Gibbs free energy required to transfer the electron from the cooper complexes to the iodobenzene is significantly high, i.e., +107.0, +118.1, and +120.2 kcal/mol for 2-NH, 2-O and 2-S, respectively. The Gibbs energy barriers of this process were estimated using the Marcus-Hush theory [70][71][72][73][74][75][76][77] within the Saveant's model [78][79][80] for the SET coupled with the cleavage of the Ph-I bond (see the Supplementary Materials pages S2-S4 for details) [51]. The activation barriers obtained are +116.0, +131.9, and +135.1 kcal/mol for 2-NH, 2-O, and 2-S, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Gibbs free energy required to transfer the electron from the cooper complexes to the iodobenzene is significantly high, i.e., +107.0, +118.1, and +120.2 kcal/mol for 2-NH, 2-O and 2-S, respectively. The Gibbs energy barriers of this process were estimated using the Marcus-Hush theory [70][71][72][73][74][75][76][77] within the Saveant's model [78][79][80] for the SET coupled with the cleavage of the Ph-I bond (see the Supplementary Materials pages S2-S4 for details) [51]. The activation barriers obtained are +116.0, +131.9, and +135.1 kcal/mol for 2-NH, 2-O, and 2-S, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The studies carried out on the reactivity of these complexes, including kinetic studies and radical clock experiments, argued against pathways involving radical intermediates. Conversely, Buchwald and Houk by experimental and computational methods claimed that the SET and HAT mechanisms are energetically more favorable for Ullmann N-and O-arylation of alkyl amines and alcohols with aryl iodides [51]. Further support to these one-electron mechanisms was given by a number of detailed theoretical studies on the N-, O-, and S-arylation reported by Zhang and co-workers [57][58][59][60][61].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[61] This type of theoretical level has proven its accuracy in the mechanistic investigations of copper-catalyzed C-N bond-forming reactions. [8,[62][63][64][65] The heats of formation of complexes with various numbers of ligands and various conformations were theoretically evaluated (see Table 2). We assumed to start that a neutral Cu I complex is formed (complexes I-V).…”
Section: The Active Copper Speciesmentioning
confidence: 99%
“…2 Buchwald, Houk, and co-workers investigate computationally the reason for the dependence on catalyst structure of the regioselectivity of N versus O in Ullmann-type reactions and provide a convincing rationalization. 3 Caflisch and co-workers report the results of molecular dynamics (MD) simulations which find that amyloid polymorphism is under kinetic rather than thermodynamic control. 4 On the basis of the results of another type of MD simulation, semiclassical trajectory calculations, Carpenter, Glowacki, and Goldman make a bold prediction about the ring-opening of bicyclo[2.1.0]-pentene.…”
Section: Editorialmentioning
confidence: 99%